Parents' language ideologies in the context of trilingual education policy in Kazakhstan - Kambatyrova, Assel (International journal of multilingualism, 2024)
Trilingual education policy is fomenting much debate among scholars and public intellectuals in Kazakhstan. However, parents' ideologies in relation to trilingual education are not heard although their participation in policy discussions is important since they play a key role in their children's education. Therefore, this article, through the lens of an adapted language ideology framework, Curdt-Christiansen [2009, Invisible and visible language planning: Ideological factors in the family language policy of Chinese immigrant families in Quebec. Language Policy, 8(4), 351-375. https://doi.org/10.1007/s10993-009-9146-7 ] examines the influence of political, economic, cultural and social, and educational factors on parents' language ideologies and ideological differences depending on the geographical location and type of school. The qualitative findings reported in this article stem from a larger mixed methods research study within which 24 interviews were conducted with parents from trilingual and mainstream schools in the North, Centre and South of Kazakhstan. The findings indicate that although the majority of parents support trilingual education policy from the political, economic and cultural perspectives, they believe that teaching in English, Kazakh and Russian should be introduced gradually to avoid negative outcomes. Studying content subjects in three languages is seen as problematic since not all children possess giftedness and abilities that are purportedly important for successful studying. Neglecting this might lead to illiterate school graduates.